The Insurance Is the Lemon: Failing to Index Contracts - HARTMAN‐GLASER, BARNEY; HÉBERT, BENJAMIN (Journal of Finance, 2020)
ABSTRACT We model the widespread failure of contracts to share risk using available indices. A borrower and lender can share risk by conditioning repayments on an index. The lender has private information about the ability of this index to measure the true state that the borrower would like to hedge. The lender is risk‐averse and thus requires a premium to insure the borrower. The borrower, however, might be paying something for nothing if the index is a poor measure of the true state. We provide sufficient conditions for this effect to cause the borrower to choose a nonindexed contract instead.